2000
DOI: 10.1063/1.1323978
|View full text |Cite
|
Sign up to set email alerts
|

Mass and size dependence of single ion dynamics in molten monohalides

Abstract: This work is concerned with four molten monohalides with different ionic radii ratios ͑RbCl, NaI, AgCl, and CuCl͒ and ideal isotopic systems of these salts with different ionic mass ratios. The velocity autocorrelation functions of the two ionic species in each melt have been studied by both a theoretical approximation and molecular dynamics simulations. It is found that their main features may be qualitatively predicted by considering suitable combinations of the second and fourth frequency moments of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The anion motion is, on the contrary, more influenced by the collisions with the other anions than by the coulombic interaction with cation. 99,115 Mixtures AgX 1 -AgX 2 /CuX 1 -CuX 2 . The difference between the silver halides and the copper halides may be attributed to the evolution of the bonding between the cation and the anion.…”
Section: Iii12 Monovalent Transition Metal Halidesmentioning
confidence: 99%
“…The anion motion is, on the contrary, more influenced by the collisions with the other anions than by the coulombic interaction with cation. 99,115 Mixtures AgX 1 -AgX 2 /CuX 1 -CuX 2 . The difference between the silver halides and the copper halides may be attributed to the evolution of the bonding between the cation and the anion.…”
Section: Iii12 Monovalent Transition Metal Halidesmentioning
confidence: 99%
“…11,12,16 Okada 16 has investigated the isotope effect by running MD simulations of ͑Li,K͒Cl in which the mass of each of the cations were made arbitrarily different. More recently, 33 an extensive study of mass and size dependence of diffusion coefficients and C v (t) in molten monohalides has been reported. Trullàs and Padró 34 have performed a systematic investigation on the difference between single particle and collective velocity correlation functions.…”
Section: Structure and Dynamics Of "Lik…nomentioning
confidence: 99%
“…12 We showed that the averaged microscopic motion of the small ions is mainly determined by the firstneighboring shell of unlike ions, whereas the nearest shell of like ions ͑the second-neighboring shell͒ also affects the dynamics of the large ions. Moreover, we showed that the difference between the cation and anion sizes encourages the backscattering and oscillations of the VACF of the large ions, whereas the mass difference encourages the vibrational motion of the light ions.…”
mentioning
confidence: 99%